PERANCANGAN SISTEM INFORMASI SERTIFIKASI KEMATIAN PASIEN RAWAT INAP BERBASIS WEB DI RSUD KOJA JAKARTA - Ina Nuraini; Lusiani Marthen; Yuda Syahidin; Yuyun Yunengsih (Bajang Institute, 2021)
In human life there will be a life cycle where humans will experience various important events in their lives, one of the important events is death. These important events need to be recorded because they greatly affect the life experience of every human being and will have legal consequences for the person concerned. A death certificate is a doctor's certificate that certifies that a person has died. A death certificate contains the identity of a person and the causes that led to the person's death. This study aims to analyze the design of an inpatient death certification information system at Koja Hospital Jakarta. The research method was carried out by descriptive method with data collection techniques by means of interviews, observation and document review related to the design of a death information system. In designing the software the author uses the waterfall method. And the supporting applications used are Web-based. From the results of the study, it is known that the implementation of making death certificates for inpatients at Koja Hospital is still done manually. There were several obstacles faced in the field, including the making of an inaccurate death report and many of the families of the patients who died asking for a copy of the death certificate because the file was lost. It is recommended that Death Certificates be made electronically in the form of designing a death certification information system and making internal and external death reports to be carried out in a computerized system so that reporting officers can report data quickly and accurately.